Translocal English in the linguascape of Mongolian popular music. Issue 1 (28th April 2016) - DOVCHIN, SENDER
ABSTRACT: This paper seeks to contribute to the current discussion of world Englishes by revealing the seamless English language incorporation in the linguascape of the popular music scene of post‐socialist Mongolia, a context that has been rarely addressed in previous research. Drawing on sets of linguistic (n)ethnographic data, the paper argues that the role of English in the mixed language practices of young musicians should be understood as 'translocal language', which makes its meaning through the contact of transnational linguistic flows and resources embedded within the idea of 'linguascape'.